Pemilihan Supplier Menggunakan Metode Analytic Network Process Di PT UTPE - Hery Hamdi Azwir; Ervin Bahar Pasaribu (Department Industrial Engineering, University of Muhammadiyah Malang, 2017)
A manufacturing company and heavy equipment attachment service provider experiencing problems in increasing production. One of its flagship products, Tipper Vessel (TV) 24m3, has constraints in terms of fulfillment of component requirements by suppliers. the company needs to add new suppliers and divide component purchases to several suppliers using more effective methods. This research uses Analytic Network Process (ANP) is effective and efficient in supplier determination. Determination of supplier company has four criteria that are rejected rate, payment transaction, delivery, and price. Data processing in the process of distributing the suppliers using questionnaires with paired comparisons and historical data about the performance of the three suppliers to be used by the company. Assisted by using Super Decisions Plus 1.6.0 software for ANP calculation, an appropriate supplier recommendation is made for certain components.